Enhancing throughput in labor intensive assembly lines - Ang Zixuan; Cheah Chew Keat; Prakash Joshua (E3S Web of Conferences)
This study aims to optimize Company X’s labor-intensive production line to significantly improve operational efficiency and reduce long-standing bottlenecks. Company X is located in Perak State, Malaysia. Comprehensive time studies and simulation analyses were conducted to identify key issues and specific bottlenecks affecting throughput and workflow. The research utilized the Single-Minute Exchange of Dies (SMED) method and simulation software to predict the next improvement solutions, significantly reducing changeover times. Simulations indicated that implementing SMED could enhance production efficiency by approximately 17%. Additionally, the study found that adding heat press (HP) pallets and upgrading various workstations could increase overall efficiency to 121%, making this approach more cost-effective and saving more resources compared to establishing a new system, which would only achieve a 100% increase in efficiency. The study recommends that Company X focus on incremental upgrades to the existing production line rather than investing in a new system. This strategy ensures a smoother transition and better leverages existing investments. Simulation software played a crucial role in evaluating proposed solutions, helping to mitigate the risks and costs associated with trial-and-error methods. Such strategic evaluations allow for more confident implementation of changes, optimizing productivity and efficiency.